PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA MTS DAN PESANTREN DI ERA NEW NORMAL - Yuliasari, Alfiyana; Anantama, Agam; Armila, Armila; Achfandhy, Mochammad Irfan (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Clean and healthy living behavior (PHBS) is an effort to spread experiences regarding healthy lifestyles through individuals, groups and the wider community with communication channels as a medium for sharing information. In the era of the new normal of the Covid-19 pandemic, clean and healthy living behaviors must continue to be applied to prevent the transmission of various diseases that cause illness and death. The main purpose of PHBS counseling is to create school communities who are health conscious and have the knowledge and awareness to live a life that maintains cleanliness and meets health standards. Counseling was carried out to 22 students of class VII MTs Riyadlatul Ulum who are also students of Islamic boarding schools. The counseling program started with an opening and remarks from representatives from the school, pre-test, counseling session, post-test, and the last closing and photo session. Overall, there is an increase of the average score from pre test and post test with the rise 0.14. Students are very enthusiastic about participating in outreach activities and it is hoped that there will be more health counseling held in their school so that students are more motivated to improve their health and the environment.